Role of curing agents in the adaptive Rresponse of the bioprotective Latilactobacillus curvatus CRL 705 from a physiologic and proteomic perspective - Teran, Lucrecia Cecilia (2023)
During meat processing, lactic acid bacteria (LAB) have to competitively adapt to the hostile environment produced by curing additives (CA). The objective of this study was to investigate the ability of Latilactobacillus curvatus CRL 705, a bioprotective strain of meat origin, to adapt to CA. A physiological and proteomic approach was performed. CRL 705 was grown in a chemically defined medium (CDM) containing specific concentrations of CA (NaCl, nitrite, sucrose, and ascorbic acid). The results showed minor differences in growth kinetics in the presence of CA. Glucose consumption, present in the CDM, and production of lactic acid and bacteriocins were not significantly affected. Proteomic analyses indicated that most of the identified proteins (36 out of 39) mainly related to carbohydrate metabolism (18%), posttranslational modifications (15.6%), energy production and conversion (11.1%), translation (11.1%), and nucleotide metabolism (8.9%) were underexpressed. In response to the studied CA, CRL 705 slowed down its general metabolism, achieving slight changes in physiological and proteomic parameters. The observed performance is another characteristic that extends the well-known competitive profile of CRL 705 as a meat starter and bioprotective culture. This is the first report dealing with the impact of CA on LAB proteomics.